Regulation of CD45 isoforms during human effector and memory CD8 T cell differentiation: Implications for T cell nomenclature - Donald J. McGuire; Rama S. Akondy; Shu Yang; Srilatha Edupuganti; Shashi Nagar; Garett Michael; Stephen C. De Rosa; Evan W. Newell; Donna L. Farber; Haydn T. Kissick; M. Juliana McElrath; Rafi Ahmed (Proceedings of the National Academy of Sciences, 2025)
This study examines the expression of CD45 isoforms on human yellow fever virus vaccine (YFV-17D) specific CD8 T cells longitudinally after vaccination. As expected, effector CD8 T cells at day 14 express CD45RO but within 4 to 6 wk these virus-specific CD8 T cells become CD45RA positive and remain CD45RA for >10 y. The journey for these YFV-specific CD8 T cells goes from naive (CD45RA+ CCR7+) to effector/effector memory (CD45RO+ CCR7−) to Temra (CD45RA+ CCR7−) to stem-cell memory (CD45RA+ CCR7+). These YFV-specific CD8 T cells rarely acquire the canonical Tcm phenotype (CD45RO+ CCR7+). This CD45RO to RA switch coincides with clearance of YFV, so we hypothesized that antigen may be playing a role in regulating CD45 expression. We addressed this issue by ex vivo analysis and provide evidence that this switch is indeed regulated by antigen. Sorted YFV-specific CD45RO effector CD8 T cells reexpress CD45RA when cultured ex vivo in the absence of antigen and retain CD45RO in the presence of cognate peptide. We also extended these ex vivo analysis to human cytomegalovirus (CMV)-specific CD8 T cells and show that CD45RO cells transition to CD45RA in the absence of antigen and CD45RA cells become CD45RO when stimulated with CMV peptide. We then show that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike-specific CD8 T cells can repeatedly undergo the same CD45RA to RO to RA transition in vivo after the SARS-CoV-2 mRNA vaccination. Again, the canonical Tcm phenotype spike-specific memory CD8 T cells were not readily detectable. These studies warrant a reevaluation of how human memory CD8 T cells are defined.